Resposta :
Resposta:
[tex]\textsf{Leia abaixo}[/tex]
Explicação passo-a-passo:
[tex]\mathsf{f(x) = 2x^2 + 5}[/tex]
[tex]\mathsf{f(-2) = 2(-2)^2 + 5 = 8 + 5 = 13}[/tex]
[tex]\mathsf{f(-3) = 2(-3)^2 + 5 = 18 + 5 = 23}[/tex]
[tex]\mathsf{f(0) = 2(0)^2 + 5 = 0 + 5 = 5}[/tex]
[tex]\mathsf{f(7) = 2(7)^2 + 5 = 98 + 5 = 103}[/tex]
[tex]\mathsf{f(3) = 2(3)^2 + 5 = 18 + 5 = 23}[/tex]
[tex]\boxed{\boxed{\textsf{Im = \{13,23,5,103\}}}}[/tex]
Resposta:
IM= {13, 23, 5, 103}
Explicação passo-a-passo:
y(-2)= 2. (-2²)+5 = 13
y(-3)= 2. (-3)²+5= 23
y(0)= 2.0²+5= 5
y(7)= 2. 7²+5= 103
y(3)= 2.3²+5= 23
Espero ter ajudado!